The Effect and Mechanism of Curcumin Combined with Carboplatin Chemotherapy Promoting on Apoptosis of Lung Cancer HCC827 Cells - Lingping Huang; Xiangyuan He; Xuan Zuo (Journal of Immunology Research)
Objective. To investigate the effect and mechanism of curcumin (CUR) killing lung cancer HCC827 cell spheres. Method. HCC827 cell spheres were cultured in serum-free medium, and the protein expression of CD133, SOX2, EpCAM, and ABCG2 was detected by western blot. MTT was used to evaluate the cell viability of HCC827 cell spheres and HCC827 cell after they were treated by 1, 2, 5, 10, and 20 mg/mL carboplatin (CBP) for 48 h. The inhibitory effects of 10 μM, 50 μM, 100 μM, and 200 μM CUR on GST (glutathione S-transferase) activity in HCC827 cell spheres were determined by colorimetry. The flow cytometry (FCM), western blot, qPCR, luciferase assay, and microscopy were used to detect the ROS levels, cell pelletization ability, β-catenin, SOX2, and ABCG2 mRNA and the promoter activity of β-catenin upon of HCC827 cell spheres treated with 200 μM CUR for 48 h. The HCC827 cell spheres were infected with β-catenin adenovirus, and then cells were treated with 200 μM CUR (and/or no 5 mg/mL CBP) for 24 h. The mRNA and protein expression of β-catenin, SOX2, and ABCG2 was detected by qPCR and western blot, and cell growth inhibition of HCC827 cell spheres was evaluated by MTT. Result. The expression of stem cells marker CD133, SOX2, EpCAM, and drug resistance-related gene ABCG2 mRNA is higher in HCC827 cell spheres, and HCC827 cell spheres resisted the killing effect of difference doses of CBP. The activity of GST of HCC827 cell spheres was inhibited by 10 μM, 50 μM, 100 μM, and 200 μM CUR. It was a dose-dependent manner. After 200 μM CUR had treated HCC827 cell spheres for 48 h, the level of ROS was significantly increased (P<0.05), and the mRNA and protein expression of β-catenin, SOX2, and ABCG2 and promoter activity of β-catenin were notably decreased (P<0.05), compared to the control group. Furthermore, the formed-sphere ability of HCC827 sphere was inhibited after cells were treated with 200 μM CUR. 200 μM CUR could suppress the proliferation of HCC827 cell spheres and induced cell apoptosis. The proliferation of HCC827 cell spheres was significantly inhibited, and cell apoptosis rate was increased by 200 μM CUR combined with 5 mg/mL CBP than by 200 μM CUR alone. Upregulation of β-catenin by adenovirus partly reversed the effect of CUR inhibition of the expression of β-catenin, SOX2, and ABCG2, compared to empty vector adenovirus group. Additionally, overexpression of β-catenin significantly remitted the inhibitory effect of 200 μM CUR combined with 5 mg/mL CBP on the proliferation of HCC827 cell spheres. Conclusion. CUR inhibited the cell proliferation and stem cell trait and induced apoptosis in HCC827 cell spheres by the inhibition of GST activity and β-catenin expression. CUR is expected to become a treatment for lung cancer and lung cancer stem cells.